2009
DOI: 10.1177/1362168809341520
|View full text |Cite
|
Sign up to set email alerts
|

Listening to our learners' voices: what demotivates Japanese high school students?

Abstract: Interview guides and a questionnaire were developed in order to find what f actors demotivated students in Japanese high school English classrooms. Five college students who were attending two private universities and one public university shared their views about demotivation in the interviews. Forty-two students at a public university responded to a questionnaire consisting of mainly open-ended response questions. Through qualitative analysis five factors were found: (1) individual teacher behavior in classr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
107
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 11 publications
13
107
1
6
Order By: Relevance
“…Therefore, Factor 1 is named as "teaching material, teaching content and teaching process". This echoes Kikuchi (2009) that the teaching mode is the inducement of demotivation.…”
Section: Answers To Research Questionmentioning
confidence: 69%
“…Therefore, Factor 1 is named as "teaching material, teaching content and teaching process". This echoes Kikuchi (2009) that the teaching mode is the inducement of demotivation.…”
Section: Answers To Research Questionmentioning
confidence: 69%
“…Moreover, when the results of the studies done in other countries were compared with this study, factors such as "interference of another foreign language being studied" (Dörnyei, 1998, "punishments" , "grammar-translation" (Falout et al, 2009;Kikuchi, 2009), "simultaneous learning of other languages" (Alavania & Sehat, 2012), "focus on difficult grammar" and "attitudes towards English speaking community" (Dörnyei, 1998Falaut & Maruyama, 2004;Kaivanpanah & Ghasemi, 2011 ) were not seen in this study. This may be attributed to the fact that these factors can be peculiar to the English-language learning context in the countries (and even in the very schools) the studies were conducted .…”
Section: Discussionmentioning
confidence: 95%
“…Zbog toga da bi učenici bili uspješni u učenju ciljnoga jezika, ključno je da su visoko motivirani. Međutim, motivacija učenika podložna je mnogim negativnim utjecajima dok traje proces učenja ciljnoga jezika (Dörnyei i Ushioda, 2011;Falout, Elwood, i Hood, 2009;Falout i Maruyama, 2004;Kikuchi, 2009;Kikuchi i Sakai, 2009). Ti utjecaji umanjuju njihovu motivaciju na početku procesa učenja jezika.…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Perhaps students feel a "permanent sense of crisis" (Ryan, 2009, p. 407) because of the dissonances and tension between English for tests and English for communication. Recent studies on de-motivation conducted in Japan reported that English classes often cause students to lose motivation (Hasegawa, 2004;Ikeno, 2002;Kikuchi, 2009). It is thought that these de-motivated students bring pain and negative feeling into new classrooms.…”
mentioning
confidence: 99%